Radio Mentari FM Solo's Strategy in Maintaining Listener Interest in The Digitalization Era and Learning Implications in High School - Rozin, Yusuf; Markhamah, M; Wahyudi, Agus Budi (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This research is motivated by how communication media that only rely on sound or audio, namely radio, can maintain listener interest in the era of globalization. The objectives of this research are (1) to be able to describe the digitalization of broadcasting that has been carried out by Radio Mentari FM Solo. (2) to describe the strategy of Radio Mentari FM Solo in maintaining listeners' interest in the digitalization era. (3) to explain the impact of the strategies that have been implemented by Radio Mentari FM. The research method used in this research is descriptive qualitative. Methodology: The research method used in this research is descriptive qualitative. The data collection technique was carried out using the interview method. Data processing and analysis techniques are carried out by means of qualitative analysis. Results: Based on the research that has been conducted, it is found that Mentari FM Radio has carried out digitalization and broadcast strategies as well as the impact caused by Mentari FM Radio in maintaining listener interest in the digitalization era. Not only maintaining listener interest, Mentari FM also provides services for listeners to provide aspirations and opinions through services, namely telephone and SMS or WhatsApp. Mentari FM also provides services in the form of streaming radio that can be listened to anytime and anywhere that can be accessed via smartphone. Applications/Originality/Value: In this case this research can be focused on high school level Indonesian language learning for students to train and improve language productive skills, namely speaking skills. The learning outcomes that can be developed by teachers in this case are that students are able to create expressions in accordance with the norms of politeness in communication. This speaking skill will be able to help students to be more confident and courageous to convey their expressions and ideas.